SOIL AND FOLIAR APPLICATION OF BORON ON WHEAT PRODUCTIVITY IN NORTH EAST ALLUVIAL PLAIN OF EASTERN INDIA - A. K. MAURIYA,; V. K. MAURYA,; R. K. VERMA,; SUNITA KUSHWAHA,; RADHEY SHYAM, (The Bioscan, 2018)
An on-farm trials was conducted during rabi season of 2013 in a randomized block design with six treatments on boron deficits soil at farmer’s field by KVK Purnea (Bihar) to validate, refine and popularize the technology developed at Bihar Agricultural University Sabour, Bhagalpur (Bihar) for enhancing the productivity of wheat [Triticum aestivum (L.) emend. Fiori & Paol.]. Application of 2.0 Kg/ha B as basal followed by 0.2% foliar application of B at 2-5 % spike initiation gave significant increase in yield attributes of wheat as compared to farmer’s practice (i.e. without boron application). The highest grain yield (3.58 t/ha) was observed where boron was applied 2.0 Kg/ha as basal fb 0.2% foliar application at 2-5 % spike initiation and it was most economical to increase wheat productivity